Some key problems on estimation of height of water-conducting fractured zone for thick coal seam top coal caving - CUI Ximin; CHE Yuhang; SUN Shuaihui; LI Peixian; SUN Hao; XU Zhihua; YUAN Debao; JIANG Jinbao; ZHAO Yuling; MALINOWSKA A (矿业科学学报, 2025)
The height of water-conducting fractured zone is an important indicator for ensuring safe mining of coal resources under water bodies. In view of the problems and deficiencies to quote empirical formula for top coal caving in thick coal seams, the basis of the empirical formula is analyzed and the applicable conditions, which are large mining areas, single-layer mining thickness of 1~3 m, and cumulative mining thickness not exceed 15 m for coal seam slice mining, are clarified and emphasized. Based on the field measurement results of the top coal caving property and top coal recovery rate, the concept of effective mining thickness for top coal caving in thick coal seams is proposed. The effective mining thickness is closely related to the recovery rate of the top coal caving and the height of the water-conducting fractured zone increases with the increase of the effective mining thickness. It is shown that the height of the water-conducting fractured zone based on the effective mining thickness can effectively avoid the underestimation caused by the increase of the top coal recovery rate in top coal caving. Based on the evolutionary law of the overburden and surface subsidence from subcritical to critical or supercritical mining, the Boltzmann function is introduced to express the relationship between the critical mining degree and the height of water-conducting fractured zone. A method for calculating the maximum height of the water-conducting fractured zone is provided based on the degree of critical mining. Taking fully into account of the recovery rate of the top coal caving and the degree of critical mining, a technical reference is provided for scientifically calculating the maximum height of the water-conducting fractured zone in thick coal seam top coal caving and the safe mining under water bodies or aquifers can be ensured.